The needs and experiences of mothers while in prison and post-release: a rapid review and thematic synthesis - Erica Breuer; Marc Remond; Stacey Lighton; Jane Passalaqua; Jennifer Galouzis; Kelly-Anne Stewart; Elizabeth Sullivan (BMC, 2021)
Abstract Background Women in prison are a vulnerable group, often with a history of abuse, out-of-home care, mental health problems and unemployment. Many are mothers when they become involved in the criminal justice system and their gender and parenting related needs are often not considered. The aim of this rapid review was to thematically synthesize the existing research on the needs and experiences of mothers while in, and following release from, prison in Australia. Methods We conducted a rapid systematic search of electronic databases, search engines, the websites of key agencies, and contacted key agencies and researchers. Results Twenty-two publications from 12 studies met the inclusion criteria and were thematically synthesized in relation to the mothers, their children, family and community, and systems and services which mothers had contact with. We found that mothers in prison have a history of disadvantage which is perpetuated by the trauma of imprisonment. Release from prison is a particularly challenging time for mothers. In relation to their children, the included studies showed that the imprisonment of mothers impacts their maternal identity and role and disrupts the mother-child relationship. Specific strategies are needed to maintain the mother-child relationship, and to ensure the needs and rights of the child are met. In relation to family and community, we found that although family and social support is an important need of women in prison, such support may not be available. Moreover, the stigma associated with having been in prison is a significant barrier to transitions into the community, including finding employment and housing. In relation to systems and services, although limited services exist to support women in prison and on release, these often do not consider the parenting role. Evaluations of parenting programs in prison found them to be acceptable and beneficial to participants but barriers to access limit the number of women who can participate. Conclusion Mothers have gender- and parenting-specific needs which should be considered in planning for corrective services in Australia. Any service redesign must place the woman and her children at the centre of the service.